THE EFFECT OF PARENTING PATTERNS AND BIRTH ORDER TOWARDS THE INDEPENDENT SOCIAL BEHAVIOR OF KINDERGARTEN CHILDREN IN GUGUS ANGGREK, EAST BANJARMASIN DISTRICT - Rakhmawati; Effendi, Rustam; Darmiyati (Journal of K6, Education and Management, 2019)
The problems that occur at this time are many children who are still dependent on their parents to do every activity. Independent attitude is very dependent on parents, often children cry when they stay for a while by their mother or caregiver. This study describes the influence of parenting on the birth order of children towards independent social behavior using a quantitative and path analysis. The research sample was obtained from 214 children aged 5-6 years using the simple random sampling technique and the Slovin formula from a population of 445 Kindergarten children in Gugus Anggrek, East Banjarmasin District. Also, data were collected through questionnaires, documentation, and observation. The results showed that parenting patterns affect the birth order of children towards their independent social behavior.